On Comparability of Theories - Valevičius, Vytautas (Problemos, 1982)
A study of scientific knowledge development presupposes an observation of the question on the interrelation between the old theory and the new one. The dialectical viewpoint indicates a definite interrelation between these theories, but the mechanism of their comparison remains unknown. Comparing the theories of science presupposes the availability of estimation criteria. To construct the latter, the structure of the given science theory must be known. A definite outline of scientific theory with general features of comparing science theories is presented by the author of the article basing on a study of the science models of logical positivism and “historical” school.